The Impact of Communication Skills Training on Social Empowerment and Social Adjustment of Slow-paced Adolescents - Mohammad Tahan; Masume Kalantari; Tahereh Sajedi Rad; Mohammad Javad Aghel; Maryam Afshari; Azam Sabri (LED Edizioni Universitarie, 2020)
The present study was an attempt to investigate the effect of communication skills training on social empowerment and social adjustment of so-called «slow-paced» adolescents (ie those whoo need psychological, physical and emotional drivers to actualize their potential abilities). The research method was a control-Group Pretest-Posttest Quasi-Experimental design. The population of the study consisted of all slow-paced female students aged 13-15 years in Ghaenat city (South Khorasan Province) during 2019. 24 samples selected from the population through convenient sampling were randomly assigned to two experimental and control groups (12 individuals in each group). Teachers or parents of both subject groups were asked to fill the questionnaires (pre-test). In the next step, the experimental group was presented with ten 45-minute sessions on communication skills, and the control group did not receive any training. In the end, both groups responded to the research instrument (post-test). Vineland social maturity scale was used as the data collection instrument. The collected data were analyzed through covariance analysis using SPSS software version 22. The results showed that communication skills training has a significant impact on social empowerment (F = 15.47, p = 0.001) and social adjustment (F = 49.64, p = 0.001). In other words, it can be argued that the experimental and control groups significantly differ from each other in terms of the communication skills training impacts on social empowerment and its components as well as social maturity. In conclusion, communication skills training significantly improves the social empowerment and social maturity of slow-paced female adolescents in the experimental group.